AB1063 Assessment of Malnutrition Risk among Patients with Rheumatologic Diseases in the Outpatient Clinics of A Tertiary Government Training Hospital in the Philippines. (10th June 2014) - Limgenco-Hipe, J.R.; Salido, E.; Magbitang, A.
Abstract : Background: Malnutrition is a frequently unaddressed confounding problemamong patients with chronic illnesses. It correlateswith decreased functionality and quality of life, and increased morbidity and mortality. The prevalence of malnutrition among patients with rheumatologic conditions ranges from 15-24%. Although there is a suspicion that malnutrition is common among Filipino patients with rheumatic diseases, there is no published data. The study will bridge this knowledge gap and hope to pave the way for a more holistic approach in the care of Filipino patients with rheumatic diseases. Objectives: To assess the risk of malnutrition among patients with various rheumatologic conditions who attend the outpatient clinics of a tertiary training government hospital in the Philippines. Methods: This is a cross sectional study of adult patients seen in a rheumatology out-patient clinic. After getting an informed consent, we collected data on demographics and disease characteristics then administered the Malnutrition Universal Screening Tool by getting their Body Mass Index, unplanned weight loss and acute disease effect score. Then we classified them according to malnutrition risk and managed accordingly. Results: One hundred eighty-two patients are included (86% are female), with mean age of 45 years old (SD 16.65). The majority (54%) have low level of education and 76% are below minimum wage earners. Twelve percent are smokers and 16% are alcohol beverage drinkers. Thirty-nine percent have systemic lupus erythematosus (SLE), 15% have osteoarthritis (OA) and 14% have rheumatoid arthritis (RA). The average duration of illness is 75 months. Ten percent of our patients are at high risk of malnutrition while 18% and 72% are at moderate and low risk, respectively. Six percent of SLE patients have high risk and 24% are at moderate risk of malnutrition. Among patients with OA, 6.9% have high and 3.4% have moderate risk of malnutrition. While patients with RA, 19% and 16% have high and moderate risk of malnutrition, respectively. Conclusions: Twenty-eight percent of patients with rheumatologic conditions being seen at the outpatient clinics of the Philippine General Hospital have moderate to high risk of malnutrition.The Malnutrition Universal Screening Tool can be used in the routine evaluation of our patients, identifying those who are at risk of malnutrition. This will allow for timely intervention and optimal care. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3520